2021
DOI: 10.1111/jse.12810
|View full text |Cite
|
Sign up to set email alerts
|

Natural interploidy hybridization among the key taxa involved in the origin of horticultural chrysanthemums

Abstract: Understanding hybridization and introgression between natural plant populations can give important insights into the origins of cultivated species. Recent studies suggest differences in ploidy might not create such strong reproductive barriers as once thought, and thus studies into cultivated origins should examine all co‐occurring taxa, including those with contrasting ploidy levels. Here, we characterized hybridization between Chrysanthemum indicum L., Chrysanthemum vestitum (Hemsley) Ling and Chrysanthemum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
2
13
1
Order By: Relevance
“…Our phylogenetic analyses of cp genomes revealed that all chrysanthemum cultivars formed a strongly supported clade (BS = 100, BI = 1.00), and shared 64 substitutions that were distinct from wild species of the genus Chrysanthemum ( Supplementary Data 1 ). This result is consistent with the suggestion that an extinct or un-sampled wild Chrysanthemum species served as the maternal donor of chrysanthemum cultivars ( Ma et al, 2020 ; Qi et al, 2021 ). This conclusion, however, depends on the assumption that cpDNA variations of chrysanthemum cultivars and wild species have been well represented in phylogenetic analyses.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our phylogenetic analyses of cp genomes revealed that all chrysanthemum cultivars formed a strongly supported clade (BS = 100, BI = 1.00), and shared 64 substitutions that were distinct from wild species of the genus Chrysanthemum ( Supplementary Data 1 ). This result is consistent with the suggestion that an extinct or un-sampled wild Chrysanthemum species served as the maternal donor of chrysanthemum cultivars ( Ma et al, 2020 ; Qi et al, 2021 ). This conclusion, however, depends on the assumption that cpDNA variations of chrysanthemum cultivars and wild species have been well represented in phylogenetic analyses.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we collected 36 accessions to represent common cultivars of different countries and different flower morphologies. Our sample size is much larger than previous studies (12 accessions; Ma et al, 2020 ; Qi et al, 2021 ), and should comprise most, if not all, of the cpDNA variations in chrysanthemum cultivars. Domesticated chrysanthemum was thought to originate from multiple species, such as C. argyrophyllum , C. indicum , C. lavandulifolium , C. nankingense , C. vestitum , and C. zawadskii ( Chen, 1985 ; Dai et al, 1998 ; Ma et al, 2020 ; Qi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations